2015
DOI: 10.1111/bju.12966
|View full text |Cite
|
Sign up to set email alerts
|

Time to replace prostate‐specific antigen (PSA) with the Prostate Health Index (PHI)? Yet more evidence that the PHI consistently outperforms PSA across diverse populations

Abstract: The Prostate Health Index (PHI) has regulatory approval in >50 countries worldwide and is now being incorporated into prostate cancer guidelines; for example, the 2014 National Comprehensive Cancer Network Guidelines for early prostate cancer detection discuss the PHI as a means to improve specificity, using a threshold score of 35 [1]. The PHI is also discussed in the Melbourne Consensus Statement [2], and it has been incorporated into the multivariable Rotterdam risk calculator smartphone app for use in poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…These findings are exactly what we would expect, as studies have consistently shown that the PHI outperforms PSA [2,6]. Other groups from the European Randomized Study of Screening for Prostate Cancer (ERSPC) have also integrated the PHI into multivariable risk prediction through the development of a user-friendly smartphone app called the Rotterdam Risk Calculator [7].…”
supporting
confidence: 68%
“…These findings are exactly what we would expect, as studies have consistently shown that the PHI outperforms PSA [2,6]. Other groups from the European Randomized Study of Screening for Prostate Cancer (ERSPC) have also integrated the PHI into multivariable risk prediction through the development of a user-friendly smartphone app called the Rotterdam Risk Calculator [7].…”
supporting
confidence: 68%
“…The tPSA levels of 22 (4.62%) men showed an abnormal level (above 10 ng ml −1 ), and those of 12 (2.52%) men were found to be in the diagnostic gray zone (4.0–10.0 ng ml −1 ) 34. These 34 men were excluded from the present study and were referred for further extensive medical diagnostics or long-term follow-up.…”
Section: Resultsmentioning
confidence: 94%
“…In general, elderly patients experience a higher incidence of PCa, which has become the second leading cause of death in some countries 34. As a result, research efforts toward screening and early detection of PCa have increased greatly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PHI score has been reported to correlate with PSA serum levels and Gleason scores. Nowadays, PHI has regulatory approval in more than 50 countries worldwide and is now being incorporated into prostate cancer guidelines for early prostate cancer detection and risk stratification [18]. However, others studies do not completely agree with these results and indicated that when the goal is to detect at least 95% of the aggressive tumors, PHI does not seem to be much more effective than the %fPSA and the PSA density [19].…”
Section: Introductionmentioning
confidence: 99%